Applications of perioperative and critical care ultrasound - Quintana Puerta, Julián Esteban (Colombian Journal of Anesthesiology, 2014)
As an extension to the physical exam, point of care ultrasonography is a tool with multiple applications. Widely used for regional anesthesia, there is not enough diffusion among anesthesiologist of the multiple possibilities that echography gives to them. This article was written to help spreading the multiple applications that ultrasound has in anesthesia, critical care and pain management.